(untitled) (Journal of Hama University, 2023)
This study aimed to recognize reading comprehersion skills which should be available in the textbook "Arabic is my language" for grades five and six of basic education, and to analyze the two textbooks according to the criterion which the researcher built, to know the level of its availability in the textbook. To chieve this aim, she followed the analytical descriptive approach by using the searching tool of the criterion of analyzing the textbook that included reading comprehension skills. The research had come to this result: First: in grade five: the constructive level got the first rank, and in the second rank the literal level, in the third rank the appreciation level, in the fourth rank the creative level, in the fifth rank the critical level. In the grade six: the constructive level got the first rank, and in the second rank the literal level, in the third rank the appreciation level, in the fourth rank the critical level, in the fifth rank the creative level.